2020
DOI: 10.21887/ijvsbt.16.1.11
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Conception Rate in AI Bred Cattle under Field Conditions of Maharashtra

Abstract: Data on 98336 artificial inseminations (AI) performed during 6 years (January 2010 to November 2015) on 56037 field animals owned by 29097 farmers’ from 44 cattle development centres spread across two districts of Maharashtra state were collected and analyzed. Whole data set was classified according to districts (Beed, Jalgaon), economic status of farmers (APL, BPL), animal breed (HF cross, Indigenous, Jersey cross, Non-descript), parity of animal (heifer, first, second, third, fourth, fifth calvers), animal b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
1
1
Order By: Relevance
“…First service pregnancy rate is an indicator which determine the quality of artificial insemination in herds. The first service pregnancy rate of approximately 38% observed in this study in control groups (Table 2), was lower to that of animals from Maharashtra (Potdar et al 2020). In this study after mineral supplementation, the average effectiveness of the first service pregnancy rate increased.…”
Section: Resultscontrasting
confidence: 56%
“…First service pregnancy rate is an indicator which determine the quality of artificial insemination in herds. The first service pregnancy rate of approximately 38% observed in this study in control groups (Table 2), was lower to that of animals from Maharashtra (Potdar et al 2020). In this study after mineral supplementation, the average effectiveness of the first service pregnancy rate increased.…”
Section: Resultscontrasting
confidence: 56%
“…The incidence of sub-fertility/infertility in crossbred bulls is high compared to purebred bulls. Sire conception rate was higher in indigenous bulls (51.1%, based on 15558 AI), compared to Holstein Friesian crossbred (47.1%, based on 47396 AI) and Jersey crossbred (43.5%, based on 2751 AI) bulls ( Potdar et al, 2020 ). Another study also reported lower conception rates in crossbred bulls (41.36% in HF crossbred and 39.84% in Jersey crossbred) compared with indigenous (54.26% in Dangi and 45.23% in Khillar) and exotic (44.05% in HF and 42.22% in Jersey) purebred bulls ( Potdar et al, 2016 ).…”
Section: Magnitude Of Reproductive Problems In Crossbred Malesmentioning
confidence: 87%